CRM INNOVATION IN IMPROVING CONSUMER SERVICE AND MARKETING OPTIMIZATION - Aini, Nur; Saputra, Herman; Kifti, Wan Mariatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: The growth of information technology continues to grow rapidly, especially in the business sector in Indonesia. Every year the growth of business shops increases to 3.98 million business units in 2022 from the real industry and trade sectors. So, this makes the Tanjung Shoe Store have serious challenges that affect sales levels which gives rise to problems of decreasing sales levels because there is no effective communication media, the shop is unable to analyze customer needs and market trends, customer disappointment often arises with the shop because it still applies conventional sales, and damage or loss of store operational data. To overcome this problem, a website-based system is needed by implementing a superior CRM (Customer Relationship Management) strategy in increasing customer retention with operational data management features, discounts, chat, online ordering, so that customers get updated information. The CRM concept used is operational, analytical, and collaborative. The application of CRM in this research aims to make it easier for users and improve customer service and optimize marketing at the Tanjung Shoe Store. So, this CRM strategy is an effective solution in facing modern business challenges in improving store performance and competitiveness.Keywords: customer relationship management; customer service; optimize marketing Abstrak: Pertumbuhan teknologi informasi terus berkembang pesat terutama pada bidang bisnis di Indonesia. Setiap tahunnya pertumbuhan toko usaha semakin meningkat hingga 3,98 juta unit usaha pada tahun 2022 dari sektor rill industri dan perdagangan. Sehingga hal ini membuat Toko Sepatu Tanjung memiliki tantangan serius yang mempengaruhi tingkat penjualan yang menimbulkan permasalahan penurunan tingkat penjualan karena tidak ada media komunikasi yang efektif, toko tidak mampu menganalisis kebutuhan pelanggan dan tren pasar, sering timbul kekecewaan pelanggan terhadap toko karena masih menerapkan penjualan konvensional, dan kerusakan atau kehilangan data operasional toko. Untuk mengatasi masalah ini diperlukan sistem berbasis website dengan menerapkan strategi CRM (Customer Relationship Management) yang unggul dalam meningkatkan retensi pelanggan dengan fitur pengelolaan data operasional, diskon, chatting, pemesanan online, sehingga pelanggan mendapatkan informasi secara update. Konsep CRM yang digunakan operasional, analitis, dan kolaboratif. Penerapan CRM pada penelitian ini bertujuan untuk memudahkan pengguna dan meningkatkan pelayanan pelanggan serta mengoptimalkan pemasaran pada Toko Sepatu Tanjung. Maka strategi CRM ini menjadi solusi yang efektif dalam menghadapi tantangan bisnis modern dalam meningkatkan kinerja dan daya saing toko.Kata kunci: customer relationship management; optimalisasi pemasaran; pelayanan pelanggan